2015
DOI: 10.1007/s00702-015-1370-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesolimbic dopaminergic dysfunction in Parkinson’s disease depression: evidence from a 123I-FP-CIT SPECT investigation

Abstract: We investigated the striatal and extrastriatal DAT availability (SPM8) by [(123)I]FP-CIT-SPECT in 15 PD patients with depression and 35 PD patients without depression. A cluster with significant (p < 0.05) lower tracer binding in PD with depression was found in left cingulate cortex, persistent after correction for age, disease severity and duration, and inversely correlated with depression scores (r -0.336, p < 0.05). Our data indicate a significant association between PD depression and cingulate dopaminergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…First of all, 123 I-FP-CIT imaging was able to explore molecular fronto-striatal connectivity, as previously reported 22, 23 . As already mentioned, voxels carrying similar information were grouped by ICA in sources that can be considered as “metabolic” pattern, reflecting a similar 123 I-FP-CIT binding in the different 29 .…”
Section: Discussionmentioning
confidence: 58%
“…First of all, 123 I-FP-CIT imaging was able to explore molecular fronto-striatal connectivity, as previously reported 22, 23 . As already mentioned, voxels carrying similar information were grouped by ICA in sources that can be considered as “metabolic” pattern, reflecting a similar 123 I-FP-CIT binding in the different 29 .…”
Section: Discussionmentioning
confidence: 58%
“…For instance, previous PET studies revealed ACC hypometabolism associated with depression in PD 46, 56 . Depressed PD patients exhibited a specific loss of dopamine and noradrenaline innervation in the ACC 6, 57 . In addition, microstructural changes in the ACC bundles were related to dPD patients 58, 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PD patients demonstrating executive impairments exhibited lower prefrontal cortex activity as measured by fMRI during a working memory task [42]. An idea that grows out of this insight is that VTA dopamine loss contributes to non-motor symptoms such as depression [43]. Many of the PD patients in pathological studies in the literature, in this and previous studies, die before non-motor symptoms are routinely investigated, thus rendering it impossible to assess the significance of VTA cell loss in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies, however have shed some light on this question by documenting abnormalities in mesocortical and mesolimbic circuits. For instance, Frosini et al demonstrated decreased dopaminergic innervation of the anterior cingulate cortex in PD patients with depression as compared to PD patients without depression, measured by dopamine transporter density [43]. Moreover, extensive animal work has indicated that dopamine dysfunction in mesocortical and mesolimbic pathways can consistently impair behaviors that are impaired in PD patients [44].…”
Section: Discussionmentioning
confidence: 99%